Improving Student Learning Outcomes about Science through the Application of Guided Inquiry Learning Models Assisted by SEQIP Kits in Class VI of SD Inpres Bumi Bahari - Rugaiyah, Rugaiyah; Tellu, Andi Tanra; Rede, Amram (Universitas Tadulako, 2020)
One effort to improve the implementation of student-centered learning is through inquiry learning models. This study aims to describe the application of a guided inquiry learning model assisted by the SEQIP Kit in improving student learning outcomes in science subjects in the sixth grade of SD Inpres Bumi Bahari. The research method used classroom action, which consists of four stages, namely planning, implementation, observation, and reflection. This research was conducted at the SD InpresBumi Bahari. The research subjects were 28 students. The data collection technique uses observation and tests. Data analysis was carried out by analyzing data qualitatively and quantitatively. The results showed that there was an increase in teacher activity and student activities. Teacher activities in the first cycle were 61% enough, and cycle II increased to 81% in the excellent category. Student activities in the first cycle were 58% enough, increasing in the second cycle to 79% in the good category. Data on student learning outcomes with classical absorption (DSK) cycle I was 63.5% and classical learning completeness (CBC) was 60.5%. These results increased in the second cycle where DSK became 87.5% and KBK 87%. Based on these results, it was concluded that the application of a guided inquiry learning model assisted by the SEQIP Kit could improve science learning outcomes in the sixth grade of SD Inpres Bumi Bahari.